Neural Stem Cells in the Diabetic Brain - Tomás P. Bachor; Angela M. Suburo (Hindawi Limited, 2012)
Experimental diabetes in rodents rapidly affects the neurogenic niches of the adult brain. Moreover, behavioral disorders suggest that a similar dysfunction of the neurogenic niches most likely affects diabetic and prediabetic patients. Here, we review our present knowledge about adult neural stem cells, the methods used for their study in diabetic models, and the effects of experimental diabetes. Variations in diet and even a short hyperglycemia profoundly change the structure and the proliferative dynamics of the neurogenic niches. Moreover, alterations of diabetic neurogenic niches appear to be associated with diabetic cognitive disorders. Available evidence supports the hypothesis that, in the adult, early changes of the neurogenic niches might enhance development of the diabetic disease.